The androgynous boom. The problem of ambiguity in the 1990s in Costa Rica. - Sequeira Rovira, Paula (2023)
The article proposes the analysis of newspaper news that focuses on the ambiguity of various reports from the newspaper La República and that reported on indeterminacy, sex change, hermaphroditism, or androgyny in the 1990s. During those years, at the international level, not only economic, political, or cultural changes were accentuated in which a neoliberal vision was deepened, but also within Costa Rica the importation of cultural models from the Global North was strengthened through the construction of malls, the viewing of music videos or movies and Internet access. Within this context, two concerns about ambiguity in the reviewed news were found. First, there were the references that were linked to sex change, hermaphroditism, or cross-dressing. On the other hand, the concerns that contained more angry rebukes were concentrated in certain singers and musical groups that were proposed as ambiguous. Most of the news made references to subjects classified as men by birth assignment, which proposed a marked interest in indeterminate masculinity. The purpose of this paper is to analyze these perceptions of ambiguity in order to highlight the tensions that were produced by the sensation of a supposed imprecision in gender, in sex, or in an indeterminate sexuality.